Genome-wide identification, phylogeny and expression analysis of AP2/ERF transcription factors family in Brachypodium distachyon. (December 2016) - Cui, Licao; Feng, Kewei; Wang, Mengxing; Wang, Meng; Deng, Pingchuan; Song, Weining; Nie, Xiaojun
Abstract Background The AP2/ERF transcription factor is one of the most important gene families in plants, which plays the vital role in regulating plant growth and development as well as in response to diverse stresses. Although AP2/ERFs have been thoroughly characterized in many plant species, little is known about this family in the model plantBrachypodium distachyon, especially those involved in the regulatory network of stress processes. Results In this study, a comprehensive genome-wide search was performed to identify AP2/ERF gene family in Brachypodium and a total of 141 BdAP2/ERFs were obtained. Phylogenetic analysis classified them into four subfamilies, of which 112 belonged to ERF, four to RAV and 24 to AP2 as well as one to soloist subfamily respectively, which was in accordance with the number of AP2 domains and gene structure analysis. Chromosomal localization, gene structure, conserved protein motif and cis-regulatory elements as well as gene duplication events analysis were further performed to systematically investigate the evolutionary features of these BdAP2/ERF genes. Furthermore, the regulatory network between BdAP2/ERF and other genes were constructed using the orthology-based method, and 39 BdAP2/ERFs were found to be involved in the regulatory network and 517 network branches were identified. The expression profiles of BdAP2/ERF during development and under diverse stresses were investigated using the available RNA-seq and microarray data and ten tissue-specific and several stress-responsive BdAP2/ERF genes were identified. Finally, 11 AP2/ERF genes were selected to validate their expressions in different tissues and under different stress treatments using RT-PCR method and results verified that these AP2/ERFs were involved in various developmental and physiological processes. Conclusions This study for the first time reported the characteristics of the BdAP2/ERF family, which will provide the invaluable information for further evolutionary and functional studies of AP2/ERF in Brachypodium, and also contribute to better understanding the molecular basis for development and stresses tolerance in this model species and beyond.